Gender-specific aspects of female forensic psychiatric evaluation - Ribeiro, Hewdy Lobo (2014)
Forensic psychiatry is the medical specialty that brings together psychiatry and law. With regard to gender-related issues, some topics have been the subject of attention in the academic literature of forensic psychiatry, e.g.: the Maria da Penha law, used mainly to assess psychiatric damage resulting from psychological violence; infanticide, characterized by the puerperal state of the mother; filicide, which may or may not be a result of maternal mental illness; and perinatal mental disorders, especially postpartum dysphoria, perinatal major depression, and postpartum psychosis. Mental health professionals should be alert to the presence of a causal relationship between mental disorders and the mother’s action or omission, as well as her understanding and selfdetermination skills while facing the event.